The welfare costs of inflation - Luca Benati; Juan Pablo Nicolini (University of Bern, Department of Economics, 2019)
We estimate the welfare costs of inflation originating from lack of liquidity satiation - as in Bailey (1956), Friedman (1969), Lucas (2000), and Ireland (2009) - for the U.S., U.K., Canada, and three countries/economic areas (Switzerland, Sweden, and the Euro area) in which interest rates have recently plunged below zero. We pay special attention to (i) the fact that, as shown by recent experience, zero cannot be taken as the effective lower bound (ELB); (ii) the possibility that, as discussed by Mulligan and Sala-i-Martin (2000), the money demand curve may become flatter at low interest rates; (iii) the functional form for money demand.; and (iv) what the most relevant proxy for the opportunity cost is. We report three main findings: (1) allowing for an empirically plausible ELB (e.g., -1%) materially increases the welfare costs compared to the standard benchmark of zero; (2) there is nearly no evidence that at low interest rates money demand curves may become flatter: rather, evidence for the U.S. (the country studied by Mulligan and Sala-i-Martin (2000)) clearly points towards a steeper curve at low rates; and (3) welfare costs are, in general, non-negligible: this is especially the case for the Euro area, Switzerland, and Sweden, which, for any level of interest rates, demand larger amounts of M1 as a fraction of GDP. For policy purposes the implication is that, ceteris paribus, inflation targets for these countries should be set at a comparatively lower level.
Keywords: 330; Wohlfahrtsökonomik; Inflationsrate; Öffentliche Sozialleistungen; Liquiditätseffekt; Eurozone; Schweden; Schweiz; USA